STRATEGI KEPOLISIAN POLRESTABES SURABAYA DALAM PENINDAKAN DAN PENCEGAHAN TINDAK PIDANA JUDI ONLINE DI KOTA SURABAYA - Dewanti, Rengganis Putri; Ismail, Ismail; Kurniawan, Bagus Ananda (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
ABSTRACT This research aims to identify the strategies of the Surabaya City Police (Polrestabes Surabaya) in handling and preventing online gambling crimes, the inhibiting factors in eradicating online gambling, and the police's efforts in law enforcement against online gambling offenders in Surabaya City. According to Article 1, paragraph 1 of Law Number 2 of 2002 on the Police, policing encompasses all matters related to the functions and institutions of the Police as well as legislation. Online gambling crimes are illegal acts and constitute a criminal offense that is prevalent in society. This research uses a qualitative method, collecting data through arguments, with purposive sampling to select samples, and analyzing the data descriptively in narrative form. The results of this research indicate that the strategy of the Surabaya City Police Criminal Investigation Unit (Satreskrim Polrestabes Surabaya) in combating online gambling through technological innovation, effective communication, and community cooperation successfully uncovered the perpetrators. Keywords: Strategy, Police, Crime, Prosecution, Gambling.